Le mystique de la vie quotidienne: An approach to the theological framework of Michel de Certeau - Trimble, BE (2022)
As scholarship engaging the interdisciplinary work of Michel de Certeau has increased since his death in 1986, there remains considerable disagreement as to what role Christian theology played in his academic career. While some scholars suggest his cultural analysis develops away from theology, other research avoids the question of his religiosity altogether. This project addresses the ways in which Certeau’s theology influenced his wider cultural analysis. In close textual studies of Certeau’s oeuvre, this project asks: what theological concerns motivated Certeau’s critical engagement with such a variety of disciplines, and what kept him from writing more overtly theological texts like his mentor, Henri de Lubac? Though Certeau rarely engages in doctrinal debates or biblical studies, I argue that Certeau’s theology forms the epistemological foundations from which he embarks on his intellectual wonderings. By discerning his key theological impetuses among his cultural analysis, this study shows a theological framework implicit within Certeau’s work on Jesuit spirituality, his socio-political writings on resistance, and his later research into psychoanalysis and spirituality. While his analysis of heterologies leads him to the limits of orthodoxy, Certeau’s implicit theology generates insights into the relationship between religious studies, theology, and the role of belief in cultural theory. To accomplish this project, I track Certeau’s theological concerns through his main spheres of cultural analysis: historiography, geography, social semiotics, psychoanalysis, mysticism, and everyday life. Through his early research with Jesuit sources, his socio-political turn in response to the student revolt in 1968, and then the final decade of his life with positions in Paris and California, I demonstrate the consistency of his inquiry into the nature of religious belief.